Inaugural Message of the “King Ferdinand I” Hall (Confluenţe Bibliologice, 2026)
The material records the inauguration of the "King Ferdinand I" Hall of the Scientific Library of the "Alecu Russo" State University of Balti, a space renovated within a project funded by the Department for Relations with the Republic of Moldova. The event highlights the importance of collaboration between institutions in Romania and the Republic of Moldova in supporting education, research and cultural dialogue, the new hall becoming a space dedicated to conferences, seminars and academic activities.
Keywords: „King Ferdinand I” Hall; international projects